1-Decylindoline-2,3-dione - Mamari, K.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title N-alkyl isatin, C(18)H(25)NO(2), the isatin moiety is almost planar (r.m.s. deviation = 0.03 angstrom). C-C-C-C torsion angles of the decyl substituent indicate an all-antiperiplanar conformation.